THE CONVERSATIONAL INFERENCE IN CEMARA’S FAMILY BY ARSWENDO ATMOWILOTO - Lia Endang Suryani; Putri Giyanwati Praditya (Dinamika Bahasa dan Budaya, 2017)
Novel is a work of fiction prose written in a narrative and usually written in story form. The word Novel is comes from the Italian "novella" which means a story or a piece of the story. The content of the novel is longer and more complex than the content of the short story, and there is no limit structural and rhyme. In general, the novel tells the story of the characters in everyday life and all the nature, character and temperament. For example is the novel of Cemara’s Family by Arswendo Atmowiloto. This novel tells about the character, story of everyday life and also the nature. In conversations between characters in this novel, there are messages or meaning that express or implied to be conveyed by the speaker. This review will discuss the Conversational inference inside the conversation in the novel Cemara's Family.Keyword: definition of novel, conversational inference, cemara’s family